Time theft in Majlis Perbandaran Sungai Petani Kedah (MPSPK) / Muhammad Shakir Zufayri Nur Hisham and Amshar Hisham Badrul Hisham - Nur Hisham, Muhammad Shakir Zufayri; Badrul Hisham, Amshar Hisham (2019)
Chapter 1 focuses on the background of the study which is time theft in workplace. It introduces the overall concept of time theft in workplace and followed by problem statement, research questions, and research objectives, scope of study, significance of study and the definition of key terms and the concepts that is used in this study. The issue of time theft came into the eye of the employers during 1983 when employees stole 15 minutes in a week and up to 5 weeks a year after Robert Half International published a report (Watt, 2009). Time theft can be defined as arriving for work 5 minutes late or leaving 5 minutes earlier, taking extended lunch breaks, unnecessary personal phone calls and emails, browsing the internet and engaging personal conversation with colleague. (Update, 2007). Back in 1983, the employees only wasted about 15 minutes a week but in current days employees steals about 30 to 45 minutes per day. Time theft is one of the major problems in organization in terms of its frequencies and financial cost. Time theft are also discussed in religious perspective. In Islam, Islam practitioners encourages its people to manage and use their time properly. This is to ensure that they are working at their best performance in order to get the blessing from Allah S.W.T.